1988
DOI: 10.1073/pnas.85.23.8850
|View full text |Cite
|
Sign up to set email alerts
|

DNA gyrase binds to the family of prokaryotic repetitive extragenic palindromic sequences.

Abstract: A family of repetitive extragenic palindromic (REP) Bacterial DNA gyrase is an essential protein, the activities of which in vitro include negatively supercoiling, catenating, and decatenating of circular DNA (6). Despite several attempts to determine the site on DNA recognized by gyrase, no clear-cut recognition sequence has been identified (7). Gyrase is thought to have multiple functions, such as involvement in DNA replication and repair, recombination, transposition, control of transcription, chromosome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
84
1
1

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 138 publications
(86 citation statements)
references
References 37 publications
0
84
1
1
Order By: Relevance
“…It is not yet known whether the degree of cleavage is correlated with the binding efficiency of DNA gyrase at these elements or whether the sequence changes affected in some way the cleavage reaction. Unlike what was observed in vitro (Yang and Ames, 1988), a single cut was observed in vivo, and in six out of seven cases was located in the Y REP. We showed that several residues were conserved in the cleavage site region of ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology, 26, 767-777 Fig. 6.…”
Section: Discussioncontrasting
confidence: 73%
“…It is not yet known whether the degree of cleavage is correlated with the binding efficiency of DNA gyrase at these elements or whether the sequence changes affected in some way the cleavage reaction. Unlike what was observed in vitro (Yang and Ames, 1988), a single cut was observed in vivo, and in six out of seven cases was located in the Y REP. We showed that several residues were conserved in the cleavage site region of ᮊ 1997 Blackwell Science Ltd, Molecular Microbiology, 26, 767-777 Fig. 6.…”
Section: Discussioncontrasting
confidence: 73%
“…Because of its stability and processive properties, the Mu SGS has been used in both rotorbead and molecular tweezers experiment to study supercoiling cycles. Unfortunately, very little is known about processivity and gyrase dynamics when gyrase is bound to sites like the BIMES of E. coli and Salmonella (Espeli and Boccard 1997;Stern et al 1984;Yang and Ames 1988). We note that when a site is too strong, it can interfere with competing DNA processes.…”
Section: What Controls Supercoil Density?mentioning
confidence: 93%
“…Additional proposed functions have related to chromosome structure (13,14,58). It has been shown that the REP sequence binds DNA gyrase (70) and DNA polymerase I (15) and that the HU protein stimulates binding of gyrase to the REP sequence (71). These studies have led to the proposal that the PU or REP sequence is involved in the folding of the bacterial nucleoid into independent supercoiled looped domains (13,58).…”
mentioning
confidence: 99%